Analisis Konsentrasi Nanoliposom Minyak Biji Alpukat (Persea americana Mill) dan Ekstrak Saffron (Crocus sativus L) terhadap Mutu Fisik Gel Nanoliposom Wound Healing : Analysis of Avocado Seed Oil (Persea americana Mill) and Saffron Extract (Crocus sativus L) Nanoliposome Concentration on the Physical Quality of Wound Healing Nanoliposome Gel - Vania, Yoshe; Aziz, Abdul; Arina Shaleha, Shinta; Naela Amalia, Berlian; Miftakhur Rohmah, Riska; Sunnah, Istianatus (Journal of Holistics and Health Sciences, 2025)
Avocado seed oil is a vegetable oil rich in fatty acids and can be used as a cosmetic, wound healing and antimicrobial. Saffron contains crocin, pirocrocetin, crocetin and safranal compounds which are useful as antioxidants so that they are widely used in the health and cosmetic fields. The application of these two ingredients will be more optimal in the form of topical nanoparticle-sized preparations. Nanoparticle preparations are considered more effective in delivering active substances of a preparation, because they can penetrate the stratum corneum layer of the skin so that the delivery of active substances is more optimal. The purpose of this study was to evaluate the physical quality of nanoliposome gels combined with avocado seed oil and saffron extract with varying concentrations of avocado seed oil nanoliposome (1% and 5%) and saffron extract (15% and 20%). The preparation of nanoliposomes used the thin-film hydration method carried out with high-energy ultraturrax. Data analysis was carried out with One-Way ANOVA in the SPSS application. The results showed that the preparation was homogeneous, thick in texture, yellow in color and had a distinctive saffron odor. The average value ± SD of the test results were pH 3.94 ± 0.25-4.19 ± 0.15; viscosity 9,912 ± 90.6-11,490 ± 567.2 cps; spreadability 4 ± 0.3-6.4 ± 0.3; adhesiveness 1.0 ± 0.1-1.12 ± 0.1 and no syneresis occurred during storage. The analysis results showed significant differences in the viscosity and spreadability tests, and no significant differences in the pH, adhesiveness and syneresis tests.   ABSTRAK Minyak biji alpukat merupakan minyak nabati yang kaya akan asam lemak dan dapat digunakan sebagai kosmetika, penyembuh luka dan antimikroba. Saffron mengandung senyawa crocin, pirocrocetin, crocetin dan safranal yang bermanfaat sebagai antioksidan sehingga banyak digunakan dalam bidang kesehatan dan kosmetik. Aplikasi kedua bahan tersebut akan lebih optimal dalam bentuk sediaan topikal ukuran nano partikel. Sediaan nano partikel dinilai lebih efektif dalam penghantaran zat aktif suatu sediaan, karena dapat menembus lapisan stratum corneum kulit sehingga penghantaran zat aktif lebih optimal. Penelitian bertujuan untuk mengevaluasi mutu fisik gel nanoliposom kombinasi minyak biji alpukat dengan ekstrak saffron dengan variasi konsentrasi nanoliposom minyak biji alpukat (1% dan 5%) serta ekstrak saffron (15% dan 20%). Pembuatan nanoliposom menggunakan metode thin-film hydration yang dilakukan dengan energi tinggi ultraturrax. Analisis data dilakukan dengan ANOVA One-Way pada aplikasi SPSS. Hasil penelitian menunjukkan bahwa sediaan homogen, tekstur kental, berwarna kuning dan bau khas saffron. Nilai rata-rata±SD hasil pengujian yaitu pH 3,94±0,25-4,19±0,15;viskositas  9.912±90,6-11.490±567,2 cps; daya sebar 4±0,3-6,4±0,3 ; daya lekat 1,0±0,1-1,12±0,1 dan serta tidak terjadi sineresis selama 72 jam penyimpanan. Hasil analisis menunjukkan adanya perbedaan signifikan pada uji viskositas dan daya sebar, serta tidak ada perbedaan signifikan pada uji pH, daya lekat dan sineresis.